The use of Monitoring in teaching as a proponent of knowledge (Research, Society and Development, 2020)
The monitoring activities were created with the purpose of acting as facilitators of the knowledge from the aid to the didactic functions of the teachers. In this context, it is urgent to understand if, in the current higher education scenario, the execution of monitoring activities favor the teaching-learning process? This study aims to elucidate the use of monitoring in teaching as a proponent of knowledge expansion, as well as to point out the positive points that the practice of monitoring brings the academic community in general (students, teachers and monitors) and demonstrate possible failures that monitoring programs can present. This is an integrative review of the literature in seven stages. Twenty articles were analyzed, five of them being chosen for the discussion. The monitoring represents a strong tool in the construction of knowledge, since it allows not only the revision of contents, but also to solve doubts, the theoretical deepening in topics of interest, the practical experience, the scientific initiation and the encouragement to teaching. However, negligence was observed in the supervisor-monitor relationship, a fact that can de-structure the teaching-learning process targeted in the monitoring programs.